Recurrent neurogenic pulmonary edema following tonic-clonic seizures - Tiwary, Manish Kumar; Manhas, Yogesh (International Journal of Research in Medical Sciences, 2024)
Neurogenic pulmonary edema (NPE) is a relatively rare life-threatening complication characterized by the acute onset of pulmonary oedema. Although many pathogenic theories have been proposed exact mechanism or aetiology is unknown. We report a case of a female patient who presented with dyspnoea following tonic-clonic seizures. Further investigations excluded cardiogenic aetiology and significant improvement in the patient within 24 h supports the diagnosis of NPE as the primary pathology. We report a case of recurrent NPE in a 24-yr old female patient with seizure disorder managed by us in our department.